2020
DOI: 10.1038/s41598-020-74563-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved NDVI based proxy leaf-fall indicator to assess rainfall sensitivity of deciduousness in the central Indian forests through remote sensing

Abstract: Quantifying the leaf-fall dynamics in the tropical deciduous forest will help in modeling regional energy balance and nutrient recycle pattern, but the traditional ground-based leaf-fall enumeration is a tedious and geographically limited approach. Therefore, there is a need for a reliable spatial proxy leaf-fall (i.e., deciduousness) indicator. In this context, this study attempted to improve the existing deciduousness metric using time-series NDVI data (MOD13Q1; 250 m; 16 days interval) and investigated its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Regional climate change can interfere with the forest ecosystem [42,43], especially the interaction with fire, which can cause serious damage to the forest [44]. In the process of studying vegetation recovery after wildfires, climate change, seasonal change, and topographic factors may affect the postfire response [45][46][47]; there was a positive correlation between NDVI and precipitation during the postfire recovery period [48]. Drought may reduce ecosystem resilience; i.e., the ability to recover the predisturbance state [49].…”
Section: Introductionmentioning
confidence: 99%
“…Regional climate change can interfere with the forest ecosystem [42,43], especially the interaction with fire, which can cause serious damage to the forest [44]. In the process of studying vegetation recovery after wildfires, climate change, seasonal change, and topographic factors may affect the postfire response [45][46][47]; there was a positive correlation between NDVI and precipitation during the postfire recovery period [48]. Drought may reduce ecosystem resilience; i.e., the ability to recover the predisturbance state [49].…”
Section: Introductionmentioning
confidence: 99%
“…The smoothed NDVI data were upscaled from 250 m to 0.05 • (~5 km) by using mean aggregation to match the spatial resolution of the rainfall data. To strengthen the analysis, we considered only the forested pixels based on a forest mask at 5 km (see Singh et al [29] for further details). A methodology representing the entire procedure involved in this study is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…First, we considered the smoothed NDVI data at 250 m resolution and then estimated mean NDVI over the entire annual cycle (NDVI-A250) and mean NDVI during the peak growth period (NDVI-P250). Generally, peak growth period refers to the period where NDVI values are greater than 50% of the maximum annual NDVI (see Singh et al [29] and Rajan and Jeganathan [67] for details). In central India, the major vegetation vigour is observed during July, August, September and October.…”
Section: Ndvi-rainfall Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…WC was also influenced by other factors, once the resistance of the controlling ability of precipitation for WC was broken, WC decreased significantly. Singh et al [84] also corroborated a high rainfall did not guarantee a high WC in a region as it depends on variety of factors. WC increased linearly with elevation and nonlinearly with TNI.…”
Section: Exploring the Driving Mechanisms Of Essmentioning
confidence: 96%